Compassionate Use of Cefiderocol as Adjunctive Treatment of Native Aortic Valve Endocarditis Due to Extremely Drug-resistant Pseudomonas aeruginosa. (12th November 2018) - Edgeworth, Jonathan D; Merante, Domenico; Patel, Sanjay; Young, Christopher; Jones, Paul; Vithlani, Seema; Wyncoll, Duncan; Roberts, Peter; Jones, Andrew; Den Nagata, Tsutae; Ariyasu, Mari; Livermore, David M; et al.
Abstract: Serious infections such as endocarditis due to extremely drug-resistance gram-negative bacteria are an increasing challenge. Here, we present successful adjunctive use of cefiderocol for a patient with persistently bacteremic healthcare-associated native aortic valve endocarditis due to an extended-spectrum beta-lactamase–positive Pseudomonas aeruginosa susceptible in vitro only to colistin, following failure of conventional therapeutic options.